Cash and In-Kind Transfers in Humanitarian Settings : A Review of Evidence and Knowledge Gaps - Jeong, Dahyeon; Trako, Iva (World Bank, Washington, DC, 2022)
Over the past decade, humanitarian assistance and social protection have increasingly emerged as a policy response tool to support crisis-affected populations facing conflict or natural disasters. This paper presents a descriptive literature review of non-contributory humanitarian assistance interventions in low-and-middle income countries. It uses evidence from twenty-one experimental or quasi-experimental studies to understand the effects on five outcome categories: (i) basic needs, (ii) financial outcomes, (iii) gender, (iv) human development, and (v) social cohesion. The findings show that gender, human development, and social cohesion are the least explored outcomes in humanitarian contexts. Moreover, evidence is scarce on the comparative performance of different modalities (for example, cash vs. in-kind), targeting mechanisms, cost-effectiveness of alternative interventions, heterogeneity analysis, and longer- term effects of interventions. The paper makes the case that there is a high dividend to be earned from conducting more impact evaluations in humanitarian settings.